Enhancing Agroecology in Pepper (Piper nigrum L.) Cultivation with Centrosema pubescens Ground Cover: A Study from Central Bangka, Indonesia - Ani Kurniawati; Sitti Nurul Aini; Nyayu Siti Khodijah; Adryade Reshi Gusta (Caraka Tani: Journal of Sustainable Agriculture, 2024)
Pepper cultivation in Bangka Island primarily takes place on sandy land. Legume cover crops, such as Centrosema pubescens, which has been widely used as a ground cover, are anticipated to improve land quality by maintaining soil temperature and humidity, increasing soil organic carbon content, increasing soil porosity, and improving soil fertility. This research aims to analyze the agroecosystem of pepper plants, by comparing the use of the cover plant C. pubescens as a soil treatment and the absence of using these cover plants as a control. The research was conducted in farmers’ pepper gardens in Perlang Village, Central Bangka Regency, Bangka Belitung Province. The research employed a randomized block design, with C. pubescens and natural vegetation as treatments, each replicated 3 times. The variables measured were soil temperature and humidity; abundance of microorganisms; weed density, frequency, and dominance; chlorophyll a, chlorophyll b, and anthocyanin content of pepper leaves; photosynthesis rate; transpiration rate; stomatal conductance; soil chemical and physical properties. The results showed that C. pubescens as ground cover could reduce the dominance of the Bidens pilosa weed (relative dominance of 36.16%) but led to an increase in the dominance of Chromolaena odorata (relative dominance of 38.7%). C. pubescens ground cover could also maintain stable soil temperature and moisture, and increase P, K, Ca, and Mg soil content by 100%, 100%, 43.6%, and 48.3%, respectively. Furthermore, pepper plants grown with C. pubescens exhibited 25%, 23.7%, and 16% higher chlorophyll a, total chlorophyll, and carotenoid content, respectively, compared to those grown without the cover crop.